Pathological and Molecular Study of Infectious Bursal Disease in Commercial Chicken - Thippani, Chandravathi; Vemuri, Rama Devi; Valeti, Samatha (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A total of 100 Poultry carcasses suspected for infectious bursal disease were collected from 20 poultry farms and conducted postmortem at the Department of Veterinary Pathology, NTR College of Veterinary science, Gannavaram ( Andra Pradesh , India) . Sick birds showed ruffled feathers, loss of appetite, whitish diarrhea and soiled vent. On postmortem examination, grossly bursa of Fabricius was swollen, enlarged with mucous exudate in lumen and haemorrhages were noticed on the mucosa. Paint brush haemorrhages were noticed on thigh muscles and at the junction of gizzard and proventriculus. Kidneys were swollen and ureters were filled with urate crystals. Histopathology of bursa of Fabricius revealed shrinkage of follicles, severe lymphoid depletion, necrosis, lymphocytolysis and cyst formation in follicles. Diagnosis of the disease was confirmed by targeting the VP2 gene of infectious bursal disease virus (IBDV) with a reverse transcriptase polymerase chain reaction which revealed an amplicon size of 743bp. Based on gross and histopathological lesions and molecular findings disease was confirmed as infectious bursal disease.